Empowered Mothers, Empowered Generations: The Impact of Women's Economic Rights - Esther Arenas-Arroyo; Elisabeth Wurm (Institute of Labor Economics (IZA), 2025)
This paper examines the long-run effects of women's economic rights on generations exposed to property and earnings acts during childhood. We find that childhood exposure to these reforms reduced the probability of marriage—particularly among women—and increased female labor force participation in adulthood. To explore potential mechanisms, we document several short-run effects among the adult generation contemporaneous to the reforms, including improved occupational standing, reduced fertility, lower child mortality, and increased schooling among children. Taken together, our findings suggest that expanding economic rights for women can shape outcomes across multiple generations, underscoring the enduring importance of legal and institutional reforms that promote women's economic empowerment.
Keywords: D13; J12; J16; N31; 330; women's economic rights; intergenerational mobility; long-run effects